Arteriovenous loops, vascular bypasses, and inflow augmentation: Enhancing limb salvage through collaboration and microsurgical creativity - Silverstein, Max; Momeni, Arash (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2025)
Limb-threatening extremity defects resulting from high-energy trauma, chronic ischemia, infection, or oncologic resection are frequently associated with a “zone of injury” devoid of suitable recipient vessels, thereby precluding conventional free tissue transfer reconstruction. In this review article, we summarize five decades of technical development and clinical evidence on advanced microsurgical strategies – such as arteriovenous (AV) loops, vascular bypasses, and nutrient flaps – aimed at restoring vascular continuity and enabling durable soft tissue coverage when local anastomosis is precluded. Regardless of the technique employed, meticulous microsurgical execution, thoughtful staging, and interdisciplinary collaboration among plastic, orthopedic, and vascular surgeons are critical to achieving optimal outcomes. Collectively, these strategies provide a versatile, evidence-based armamentarium that enables reconstructive surgeons to preserve limb length, secure durable soft tissue coverage, and restore meaningful function to extremities once considered unsalvageable.
Keywords: orthoplastic; arteriovenous loop; bypass; limb salvage